2019
DOI: 10.1021/acs.jpcc.9b03256
|View full text |Cite
|
Sign up to set email alerts
|

Cage Occupancies in Nitrogen Clathrate Hydrates from Monte Carlo Simulations

Abstract: Comparisons of Gibbs ensemble Monte Carlo simulations with experimental data for the cage occupancies in N 2 clathrate hydrates are performed to assess the accuracy of such simulations, to refine the effective potentials employed, and to help interpret recently measured large cage over small cage occupancy ratios [Petuya et al., J. Phys. Chem. C 122, 566 (2018)]. Different sets of interaction potentials for N 2 N 2 , N 2 H 2 O and H 2 O H 2 O interactions are considered. Some of them fail to reproduce the kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…The present GCMC calculations evidence the influence of the CO-water interaction model on the results, as already previously shown for N 2 . 45 Indeed, whereas the model of Piper et al (model A) 42 appears well-suited for characterizing incorporation of CO molecules into clathrates, the one proposed by Straub and Karplus 43 (model B) seems more accurate for characterizing adsorption at the surface of solid water. This enlightens the need for an interaction potential model between carbon monoxide and water molecules that could be transferable to different water environments.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The present GCMC calculations evidence the influence of the CO-water interaction model on the results, as already previously shown for N 2 . 45 Indeed, whereas the model of Piper et al (model A) 42 appears well-suited for characterizing incorporation of CO molecules into clathrates, the one proposed by Straub and Karplus 43 (model B) seems more accurate for characterizing adsorption at the surface of solid water. This enlightens the need for an interaction potential model between carbon monoxide and water molecules that could be transferable to different water environments.…”
Section: Discussionmentioning
confidence: 97%
“…On the basis of previous works devoted to trapping of CO and N 2 in clathrates, 44,45 , the water molecules have been modeled by the TIP4P-Ew model, 40 whereas the model proposed by Potoff and Siepmann on the basis of the TraPPE force field, 41 has been used for N 2 . When considering the CO molecules, two different force fields have been considered, on the basis of their ability for describing CO-water interactions in various contexts.…”
Section: Simulations Detailsmentioning
confidence: 99%
“…The volume and energies were found to be linearly dependent on the cage occupancy, and there was no marked difference in the structure between singly and doubly occupied systems. Grand-canonical Monte-Carlo studies were performed on sI and sII nitrogen clathrate hydrates. , These studies showed that at low temperature (at 50 K), the SCs are filled before the LCs, but at a higher temperature (at 150 K) the opposite happens, i.e., the LCs are filled before the SCs. Carbon monoxide hydrate has also been simulated and, in the latter case, whatever the structure formed or the temperature, the SCs were always occupied before the LCs, although at 150 K the occupancy of both types of cages becomes simultaneous.…”
Section: Introductionmentioning
confidence: 99%
“…Grand-canonical Monte-Carlo studies were performed on sI and sII nitrogen clathrate hydrates. 25,26 These studies showed that at low temperature (at 50K), the SCs are filled before the LCs, but at higher temperature (at 150K) the opposite happens, i.e. the LCs are filled before the SCs.…”
mentioning
confidence: 99%
“…The internal degrees of freedom have not been considered and, thus, all of the molecules have been treated as rigid bodies. The water molecules have been represented by the TIP4P-Ew model, 31 already used in several hydrate studies, 32,33 in which it has been shown to give satisfactory results compared to the experimental data. In this The Lennard−Jones parameters σ (size parameter) is given in Å, like all distances, whereas ε/k B (energy parameter) is given in K, with k B being the Boltzmann constant.…”
Section: Introductionmentioning
confidence: 99%